Comparison of the skin sensitization potential of 3 red and 2 black tattoo inks using interleukin‐18 as a biomarker in a reconstructed human skin model. (22nd August 2018) - Bil, Wieneke; van der Bent, Sebastiaan A. S.; Spiekstra, Sander W.; Nazmi, Kamran; Rustemeyer, Thomas; Gibbs, Susan
Abstract : Background: During the last decade, the number of people with ≥1 tattoo has increased noticeably within the European population. Despite this, limited safety information is available for tattoo inks. Objectives: To test the skin sensitization potential of 5 tattoo inks in vitro by using reconstructed human skin (RHS) and the contact sensitization biomarker interleukin (IL)‐18. Methods: Two red and 3 black tattoo inks, 1 additive ( Hamamelis virginiana extract) and 1 irritant control (lactic acid) were tested. The culture medium of RHS (reconstructed epidermis on a fibroblast‐populated collagen hydrogel) was supplemented with test substances in a dose‐dependent manner for 24 hours, after which cytotoxicity (histology; thiazolyl blue tetrazolium bromide assay) and skin sensitization potential (IL‐18 secretion; enzyme‐linked immunosorbent assay) were assessed. Results: All but 1 ink showed cytotoxicity. Notably, 1 red ink and 1 black ink were able to cause an inflammatory response, indicated by substantial release of IL‐18, suggesting that these inks may be contact sensitizers. Conclusions: The in vitro RHS model showed that 4 tattoo inks were cytotoxic and 2 were able to cause an inflammatory IL‐18 response, indicating that an individual may develop allergic contact dermatitis when exposed to these tattoo inks, as they contain contact sensitizers.